Speed-strength testing and analyzing by standing jumps in volleyball - Losev, A. V.; Schneider, V. Yu. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to provide a speed-strength testing and analyzing toolkit with application of the maximal-height and-push-off-speed prioritizing standing jumps in volleyball skills tests and trainings. Sampled for the experiment were 28 athletes whose jumping qualities were tested by MLB Biomechanics Test System. The athletes were required to jump in the tests (1) for the maximal height; (2) with the maximal push-off speed; and (3) for the 60%-maximal height. Tests under the study were designed to profile the lower limb speed-strength operation patterns versus the jump goals (height or push-off speed). The test data and analyses showed the need for the special physical training component of the training system being revised to step up the volleyball players` speed-strength qualities and build up the relevant skills with an emphasis on the match tactics versatility.